Comprehensive aroma profiles and the underlying molecular mechanisms in six grape varieties with different flavors - Wu, Guang; Xin, Yuchen; Ren, Ruihua; Chen, Huawei; Yang, Bowei; Ge, Maosheng; Xie, Sha (Frontiers in Plant Science, 2025)
Aroma is a critical factor in determining grape quality, develops through complex interactions among various volatile compounds. This study revealed the differences of the six grape varieties with three different aroma types though the HS-SPME/GC-MS and RNA-sequencing technologies. Muscat-type grapes ('Shine 13' and 'Shine Muscat') exhibited the highest monoterpene and C13-norisoprenoid level, correlating with elevated expression of DXS, TPS, and CCD4b genes in the MEP/MVA pathways. Strawberry-type cultivars (particularly 'Hutai 8') accumulated abundant esters linked to high AAT expression, while neutral aromatic varieties showed enriched C6/C9 compounds associated with upregulated LOXA and ADH2. Muscat-type grapes dominated monoterpenes with OAVs >1, which explained the abundant Muscat flavors, while neutral aromatic aroma cultivars had the most abundant C6/C9 compounds OAVs associated with leaf-like scents. Strawberry-type cultivars exhibited the highest esters OAVs with strawberry aroma profiles. WGCNA analysis revealed four specific modules correlated with aroma compound biosynthesis correlated with alcohols (88genes), carbonyl compounds (451genes), fatty acids (110 genes), and monoterpenes (790genes) accumulation in these grapes, respectively. These findings were expected to advance our understanding of the metabolic pathways responsible for grape aroma and could provide valuable recommendations for the enhancement of grape aromatic quality.